Cryopreservation of Carp Sperm (Cyprinus carpio, L. 1758) Obtained in a Prespawning Period - Butskyi, Kyrylo I.; Puhovkin, Anton Yu. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 155